1999
DOI: 10.1093/jmedent/36.6.861
|View full text |Cite
|
Sign up to set email alerts
|

Barmah Forest Virus Epidemic on the South Coast of New South Wales, Australia, 1994–1995: Viruses, Vectors, Human Cases, and Environmental Factors

Abstract: In 1995, the largest recorded outbreak of human disease resulting from infection with the mosquito transmitted alphavirus Barmah Forest (BF) virus occurred along the south coast of New South Wales, Australia. The virus was first isolated in early January from mosquitoes collected at Batemans Bay and predisposed the recognition of 135 human clinical cases. The cases of BF virus were identified initially from Batemans Bay during late January, and the majority (30%) of all cases came from this town. After 5 wk, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…For example, in 1995, the largest recorded outbreak of human disease resulting from infection by BFv occurred along the south coast of New South Wales, Australia (Doggett et al 1999), when 135 cases of BFv were notified. The outbreak appeared to be associated with several factors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in 1995, the largest recorded outbreak of human disease resulting from infection by BFv occurred along the south coast of New South Wales, Australia (Doggett et al 1999), when 135 cases of BFv were notified. The outbreak appeared to be associated with several factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although the first outbreak of BFV occurred during 1992 in the Northern Territory (Merianos et al 1992), subsequent outbreaks have been reported from southwest Western Australia in 1993(Lindsay et al 1995b, New South Wales in 1995 (Doggett et al 1999), and Victoria in 2002 (Passmore et al 2002). The 2005-2006 period marked the largest BFV epidemic on record in Australia, with 1,895 notifications (Liu et al 2006).…”
Section: History Of Epidemic Polyarthritis In the Australasian Regionmentioning
confidence: 99%
“…Muhar et al (2000) found that risk of Ross River virus in Brisbane, Australia was significantly related to several wetland habitats including intertidal and freshwater ones associated with floodplains. More recently, Barmah Forest virus has become a public health issue in Australia, with symptoms similar to Ross River virus and the two diseases have some mosquito vectors in common (Doggett et al 1999;Quinn et al 2005).…”
Section: Ross River and Barmah Forest Virusesmentioning
confidence: 99%